ANALISIS SWOT DALAM PROSES PENERIMAAN PESERTA DIDIK BARU DI SMPN 14 KOTA JAMBI: ANALISIS SWOT DALAM PROSES PENERIMAAN PESERTA DIDIK BARU DI SMPN 14 KOTA JAMBI - Suryadi Suryadi; K.A Rahman; Marfu’ah Nursulis; Undari Sulung; Loly Nadila Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Several State Junior High Schools (SMPN) in Kotabaru District, Jambi City experienced a decline in the number of students. This is demonstrated by the results of observations and interviews. These findings indicate the need for analysis regarding student management and solutions to problems. The aim of this research is to describe the SWOT analysis of student management in accepting new students at SMPN 14 Jambi City, the solutions provided to resolve these problems. The approach in this research is descriptive. The research method used is qualitative research. Data collection using interview techniques, observation and researcher documentation. Based on the results of the SWOT analysis in accepting new students (PPDB) at SMPN 14 Jambi City, it can be said that the PPDB process is still not optimal, the number of students has not met the standard maximum quota in one group. This is because there are still many weaknesses in the program for accepting new students and the strengths and opportunities that the school has not yet optimally utilized. From the SWOT analysis several alternative solutions can be provided that can increase the strength in accepting new students at SMPN 14 Jambi City